Recycling Water Hyacinth as Supplementary Cementitious Material, Admixture, and Fiber in Mortar and Concrete: Current Trends and Research Gaps - Gilberto García; René Cabrera; Julio Rolón; Roberto Pichardo (Recycling)
This review explores the potential of water hyacinth (WH) as a sustainable material in cement-based applications, focusing on its use as an addition, admixture, and fiber reinforcement. WH’s unique physical and chemical properties, such as high cellulose content and pozzolanic potential, make it suitable for bio-composites and eco-friendly concrete formulations. The present study highlights several promising findings, including the enhancement of the resulting mechanical properties and the reduction in their environmental impact when the WH is incorporated in controlled quantities. Challenges such as workability and durability issues at higher dosages are discussed. This review aims to bridge knowledge gaps and support WH’s adoption in sustainable construction practices.